Delineating the Concept of Human Dignity in the Quran: Karamah al-insan as an Antidote to Religious Conflicts and Violence - Ali, Mohamed Bin (Advances in Social Sciences Research Journal, 2022)
Human dignity is defined as the right of every human life to be valued unconditionally. In Islam, this is perfectly embodied in the Quranic concept of “karamah al-insan” (Human Dignity). Karamah al insan becomes an instructive Islamic principle that regulates all human relationships, including those between Muslims and others. However, misperceptions in peripheral exclusivist thoughts have clouded the concept, positioning the honour and rights of the religiously faithful above those who were deemed lower by virtue of their religious choices. This paper sets out to ascertain the distinction between inherent dignity as an intrinsic right of every human being versus acquired dignity, that which is obtained by virtue of a Muslim’s efforts to ascend up the spiritual ladder. This distinction will distill the value of karamah al-insan as a universal value (human rights) and a shared belief among the different faiths. Furthermore, this clear distinction will deconstruct the claims made by extremist groups to justify civilian and religiously-motivated attacks. To this end, the paper will take a closer look at the Quranic verse 17:70, that specifically mention about human dignity and other related Quranic verses. The paper concludes with the argument that as a universally-shared value, the concept of karamah al-insan will serve as a robust antidote to social and religious chaos especially in these divisive times.